Automedicación y factores asociados al uso de antibióticos en la población asignada al Hospital Universitario de Motupe - Herrera Andrade, Tatiana Elizabeth (2020)
Self-medication is daily worldwide, in which various socio-demographic, socio-cultural and socio-economic factors play a fundamental role in this habitual practice. In recent years, self-medication has caused many germs to become resistant to antibiotics, resulting in ineffective treatments. The objective of the present investigation was to know the frequency of self-medication with antibiotics and factors associated with the population of influx to the Motupe University Hospital. The methodology used in the investigation was transversal. A sample of 375 people was selected for the application of the survey, carrying out the respective analysis, a frequency of self-medication with antibiotics of 17.33% (n = 65) of them was shown, 58.46% (n = 38) were female sex. The most used antibiotics in self-medication were Amoxicillin with the highest frequency 30.43% (n = 21), followed by Ampicillin 20.29% (n = 14). The factors that had statistical significance with a value of p <0.05 and a significant association were: lack of time to see to the doctor and no having the necessary resources to pay for a private medical consultation; difficulty for obtaining a medical appointment in health facilities; the influence of third people, such as family, friends, pharmacist and the ease of acquiring medicine in pharmacies, stores or family medicine cabinet. We conclude: self-medication with antibiotics is a multifactorial problem, with a higher prevalence in female sex. The most widely used antibiotic is Amoxicillin similar to that used in other studies. Key words: self-medication, antibiotics, predisposing factors